Energy analysis of a surfactant micelle's deformation by coarse-grained molecular dynamics simulations. (20th July 2019) - Zhou, Wenjing; Liu, Fei; Liu, Dongjie; Chen, Fei; Wei, Jinjia
Highlights: The Müller-plathe algorithm is adopted to generate deformations of a wormlike micelle. New evidence for the "viscoelastic theory" is presented at the microscopic scale. The penetrating counter ion salts are more beneficial to the turbulent drag reduction. Abstract: Surfactant molecules can self-assemble into micellar networks and be used as efficient additives in turbulent drag reduction in aqueous solutions. The mechanism of turbulent drag reduction by these percolating structures is still unclear. In particular, the "viscoelasticity theory" postulates that the micellar network structures are capable of absorbing and releasing stress from turbulent kinetic energy which results in the decrease of the energy dissipation. Here, we focus on the single wormlike surfactant micelle which consists of cetyltrimethylammonium chloride (CTAC) and counter ion salts to study the energy variation during its deformation processes using MARTINI force field coarse-grained molecular dynamics (CGMD) simulations. The Muller-Plathe method was used to generate the small and large deformation stretching statuses of the wormlike micelle through adjusting the momenta exchange frequency. The simulation results show that the micelle can transfer its potential energy to water during its relaxation stage after being stretched. It is also found that the flow field of water is significantly influenced by the recoil of micelle and a vortex is observed in the area semi-enclosed by the bending micelle. Overall, the present study supports the hypothesis of "viscoelasticity theory" and provides further insight into the mechanism of turbulent drag reduction by surfactant additives.